A Metastasis-competent CAF Subpopulation Defined by MFAP5+THY1+ Co-expression Drives Prostate Cancer Metastasis via EMT Activation - Huang, Yongqiang; Wang, Yu; Zhang, Wei; Wang, Wenfeng; Du, Leilei; Zhang, Xingming; Xu, Wenhao; Zheng, Jianghua; Shi, Guohai; Wang, Jianhua (Recent Patents on Anti-Cancer Drug Discovery, 2025)
<span class=
Keywords: cancer-associated fibroblasts